PENGARUH ASESMEN DIRI DAN MOTIVASI BERPRESTASI TERHADAP KOMPETENSI MENULIS BAHASA INGGRIS - ida nyoman basmantra (Universitas Pendidikan Nasional, 2017)
AbstractThe Effect of Self-Assessment and goal Motivation through Writing Competency in English. The purpose of this study is proving application of self-assessment in terms of student achievement motivation to give influence to the competence of writing in English students. This research was an experimental research using 2 x 2 proportional conception. Forced population of 160 students majoring in communication studies, Faculty of Social and Politics Studies, University Undiknas academic year 2016/2017. By using Cluster Random Sampling method, 4 classes were selected as sample and divided into two groups, namely experimental group and control group. The data of this study were collected through questionnaires and tests, which were analyzed using the Two Path Anova and Tukey test statistics. The results showed, firstly, the influence of self- assessment on student writing skill, ie students who assess by using self-assessment have higher writing skills than those who use using conventional assessment. Secondly, there was a significant interaction effect between self-assessment and achievement motivation on writing skill in English.Keywords: self-assessment, achievement motivation, english writing competency